Johannes Rothes Elisabethleben Aufgrund des Nachlasses von Helmut Lomnitzer - Haase, Annegret / Schubert (Deutsche Texte des Mittelalters, 2005)
The life and miracles of St. Elisabeth of Thuringia are the subject of the 'Life of Elisabeth' by the Eisenach council scribe Johannes Rothe (ca. 1360-1434). Rothe, who had already written spiritual works and three extensive chronicles ('Eisenacher Stadtchronik', 'Thüringische Landeschronik' and 'Weltchronik'), offers a comprehensive rendition of the chronicle and legendary tradition in the rhyming verse legend of over 4,000 verses, whereby, in addition to the chronicles, he particularly exploits the Latin Vita of Dietrich von Apolda. In the formal connection to the legends of the saints and the orientation towards chronicles in terms of content, Rothe adopts a cross-genre standpoint. Elisabeth's life is integrated into the genealogy of the landgrave's dynasty and thus becomes part of the landgrave's memorial culture. In the history of the text's reception, with numerous copies up to the 18th century, there is evidence of corresponding emphases: the work was used partly as a devotional book and partly as part of the dynastic memoria of the Thuringian dynasty.